Dementia with Lewy bodies - O. S. Levin; E. E. Vasenina; A. Sh. Chimagomedova; N. G. Dudchenko (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Te lecture presents modern concept of the symptoms, diagnosis and treatment of dementia with Lewy bodies (DLB), which accounts for about 10% of cases of dementia. Te nosological status of DLB and the problem of ratio of DLB and Parkinson’s disease which, apparently, represent two phenotypic variants of one neurodegenerative process («diseases with Lewy bodies») are considered in historical aspect. Approaches to the diagnosis and coding of DLB in accordance with ICD-10 are proposed. Te role of cholinesterase inhibitors, antipsychotics, levodopa, rasagiline and other drugs in the treatment of patients with DLB is аnalyzed.